Assessing the determination of salivary electrolytes and anti-Ro and anti-La antibodies for the diagnosis of Sjogren s syndrome (SS) - Busamia, Beatriz Ester (2010)
The aim of this study was to assess changes in salivary electrolyte flow and composition and the presence of anti-Ro/SSA and anti-La/SSB serum and saliva antibodies and their implications for the non-invasive diagnosis of SS. Study design: 73 patients were studied, divided into the following experimental groups: primary Sjögren syndrome (SSp) (n=15), secondary SS (SSs) (n=17), dry mouth, dry eye without Sjögren?s syndrome (BO) (n=20) and healthy controls (C) (n=21). We conducted a baseline assessment of salivary flow and saliva sampling for the measurement of sodium, chlorine, potassium, calcium and phosphate electrolytes, and the determination of anti- Ro/SSA and La/SSB antibodies; a serum sampling was made to assess antibody positivity. Results: Salivary flow in SSp, SSs and BO was significantly lower (p<0.001) relative to C. The salivary composition of SS showed an increase of inorganic components. Anti-Ro/SSA and anti-La/SSB antibodies occurred more frequently in serum and saliva in SS patients compared with BO and C, with higher frequency of positivity in serum compared with saliva. Conclusion: Our results suggest new tools that could aid the non-traumatic diagnosis of the origin of hyposalivation.